Aproveitamento do resíduo do processamento do camarão (litopenaeus vannamei) no desenvolvimento de um novo produto - Santos Junior, Josue dos (Universidade Federal Rural do Semi-Árido, 2018)
The objective of this study was to develop a by-product (flour) from the shrimp (Litopenaeus vannamei) processing residue and use it as an ingredient in the development of new products (flavoring flour and shrimp-flavored biscuit). Analysis of centesimal composition (moisture, protein, lipids and ashes), and microbiological (thermotolerant coliforms at 45°C, Salmonella sp., Staphylococcus coagulase positive, molds and yeasts) were analyzed for the residue, flour and new products. The products (flavoring flour and shrimp-flavored biscuit) were sensorially evaluated (Global Acceptance Test and Attitude Scale Test), and then packed in modified atmosphere (100% N2) and stored for 180 days at controlled ambient temperature (25±1°C) for evaluation of shelf life. The microbiological analysis of the residues, the flour and the products were within the limits of the legislation, confirming the hygienic-sanitary care during processing. Among the components of the centesimal composition of the developed products, the highlight was the protein content (40.13% - flavoring flour, and 20.52% - shrimp-flavored biscuit). The acceptability index of the products was 72.6% for flavoring flour and 83.3% for shrimp-flavored biscuit. The results of the shelf-life study demonstrated physical-chemical and microbiological stability throughout the 180 days of storage. The results demonstrated that the residue from the shrimp Litopenaeus vannamei processing can be used as an ingredient in new food products
Keywords: Camarão; Resíduo; Novos Produtos; Shrimp; Residue; New products; CIENCIAS AGRARIAS::MEDICINA VETERINARIA